Genetic Modulation of Training and Transfer in Older Adults: BDNF Val66Met Polymorphism is Associated with Wider Useful Field of View - Colzato, Lorenza S.; van Muijden, Jesse; Band, Guido P.; Hommel, Bernhard (Frontiers in Psychology, 2011)
Western society has an increasing proportion of older adults. Increasing age is associated with a general decrease in the control over task-relevant mental processes. In the present study we investigated the possibility that successful transfer of game-based cognitive improvements to untrained tasks in elderly people is modulated by preexisting neuro-developmental factors as genetic variability related to levels of the brain-derived neurotrophic factor (BDNF), an important neuromodulator underlying cognitive processes. We trained participants, genotyped for the BDNF Val66Met polymorphism, on cognitive tasks developed to improve dynamic attention. Pre-training (baseline) and post-training measures of attentional processes (divided and selective attention) were acquired by means of the Useful Field of View (UFOV) task. As expected, Val/Val homozygous individuals showed larger beneficial transfer effects than Met/-carriers. Our findings support the idea that genetic predisposition modulates transfer effects.